(untitled) (Research, Society and Development, 2023)
Introduction: Acute Myocardial Infarction (AMI) is characterized by cellular death and necrosis in the cardiac muscle, resulting from the progression of acute ischemia, making it the leading cause of death worldwide. Objective: To understand the profile of patients admitted with a diagnosis of AMI at the Clínicas de Itajubá hospital. Methods: A retrospective, cross-sectional study was carried out, with a definitive sample of 48 patients diagnosed with AMI, admitted to the medical clinic ward at the Hospital de Clínicas de Itajubá (HCI), between December 2020 and December 2021. Results: The results obtained and analyzed were: 66.67% male; 37.5% in the 60 - 69 age group; 67.74% hypertensive; 12.9% dyslipidemic; 35.48% diabetic; Characterization of education: 2.08% illiterate, 47.92% with incomplete primary education, 14.58% complete secondary education, 6.25% incomplete secondary education and 8% have completed higher education; Lifestyle: 9.68% obesity; 47.92% were smokers and 12.5% ​​were alcoholics. Conclusion: This study expanded knowledge in the field of scientific research on acute myocardial infarction in the microregion of Itajubá, identifying data that can be used as a basis for prevention strategies and, consequently, improvements in quality of life and life expectancy.